Distorsi Simbol Islam dalam Film Horor Thaghut: Analisis Semiotika atas Potensi Stereotip Negatif - Vega Prastia; Abdul Syukur; Ade Nur Istiani (ALAMTARA, 2026)
The distortion of religious symbols in Indonesian horror films has become an increasingly prevalent phenomenon, including in the film Thaghut, which portrays various Islamic symbols such as prayer (salat), the call to prayer (azan), qibla direction, and religious authority within supernatural narratives. The communication problem addressed is how the process of distorting Islamic symbols in the film potentially shapes negative stereotypes of Islam in public perception. This study aims to analyze the forms of distortion of Islamic symbols in the film Thaghut, reveal the denotative, connotative, and myth meanings based on Roland Barthes' semiotics, and explain how such distortion potentially generates negative stereotypes from Stuart Hall's representation perspective. The research employs a qualitative approach using Roland Barthes' semiotic analysis method focused on five main scenes containing Islamic symbols. The findings reveal that Islamic symbols undergo systematic meaning distortion: the practice of prayer is represented as a moment vulnerable to possession, the azan is depicted as a source of physical suffering, the qibla direction is shown as unstable, and religious authority is constructed as a cult-like and manipulative figure. These representational distortions construct the myth that Islam is identical with irrationality, spiritual instability, and legitimation of extreme practices, potentially reinforcing negative stereotypes against Muslims. The study concludes that horror films not only function as entertainment but also as a medium of meaning production that can distort sacred symbols. The contribution of this study lies in revealing the mechanism of distortion of Islamic symbols in Indonesian horror films through an integrated semiotic approach, as well as providing critical awareness for audiences and media regulators